Secret operations of World War II the clandestine battle fought across occupied countries by the SOE, OSS, Maquis, partisans and resistance fighters - Stilwell, Alexander (Amber Books, 2018)
How were agents recruited for secret operations in World War II? How did they fare once dropped behind enemy lines? How effective were resistance movements? And how brutal were the reprisals? Ranging from the American Office of Strategic Services (OSS), the British Special Operations Executive (SOE) and the German Abwehr to resistance movements across Europe, Secret Operations of World War II is a fascinating account of the major special ops organisations and underground cells in the conflict. Examining recruitment, training, equipment and deployment of operatives, the book not only reveals the ingenious steps taken to select suitable agents, disguise weapons and gather intelligence, but also follows the fortunes of particular agents after their operations were launched. From such well known cases as the SOE and Norwegian agents sabotaging Norwegian hydroelectric plants to the less explored territory of Soviet partisans, from the Abwehr's rescue of Mussolini to the French Maquis, from the Polish Home Army to OSS operations in the Pacific, the book explores a wide range of secret organisations and their intelligence gathering, sabotage and reconnaissance missions. Illustrated with 120 black-&-white and colour photographs, artworks and maps, Secret Operations of World War II is an authoritative and novel perspective on some of the most outlandish episodes of the conflict.